Imagined Affordance: Reconstructing a Keyword for Communication Theory. (22nd September 2015) - Nagy, Peter; Neff, Gina
In this essay, we reconstruct a keyword for communication—affordance. Affordance, adopted from ecological psychology, is now widely used in technology studies, yet the term lacks a clear definition. This is especially problematic for scholars grappling with how to theorize the relationship between technology and sociality for complex socio-technical systems such as machine-learning algorithms, pervasive computing, the Internet of Things, and other such "smart" innovations. Within technology studies, emerging theories of materiality, affect, and mediation all necessitate a richer and more nuanced definition for affordance than the field currently uses. To solve this, we develop the concept of imagined affordance. Imagined affordances emerge between users' perceptions, attitudes, and expectations; between the materiality and functionality of technologies; and between the intentions and perceptions of designers. We use imagined affordance to evoke the importance of imagination in affordances—expectations for technology that are not fully realized in conscious, rational knowledge. We also use imagined affordance to distinguish our process-oriented, socio-technical definition of affordance from the "imagined" consensus of the field around a flimsier use of the term. We also use it in order to better capture the importance of mediation, materiality, and affect. We suggest that imagined affordance helps to theorize the duality of materiality and communication technology: namely, that people shape their media environments, perceive them, and have agency within them because of imagined affordances.